Motivating students to learn - Brophy, Jere E. (New York : Routledge, 2010)
Although this book offers theories that explain students' motivational orientations, it focuses primarily on strategies teachers can use to optimize those orientations and direct them towards the academic learning goals of the school.
Includes bibliographical references and indexes.
Keywords: Motivation in education